MOLECULAR TECHNIQUES FOR DETECTION OF AFLATOXIGENIC ASPERGILLUS FLAVUS AND DETERMINE THEIR AFLATOXIN IN PISTACHIOS. - K.I.Hassan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The better approach to control the contamination of food by aflatoxin (AF), is identifying the fungal strains responsible for producing that toxin. To estimate the presence of aflatoxigenic fungi growth and AFs in pistachios, thirty two pistachios samples (8 fresh and 24 salt roasted) were collected from Sulaimani markets (Iraq).Rapid screening method for AFs production were utilized initially based on culture methods, the positive samples confirmed by polymerase chain reaction (PCR) that were applied using DNA extracted from the isolates of A. flavus targeting the genes (afR, aflP, aflD, and aflQ). For determination of AF production of those isolates, ELISA technique was applied. The results show, contamination of 20 (62.5%) samples of pistachios with fungi, among them A. flavus was the predominant. Ten (71.4% (of the A. flavus isolates were amplified the target genes by applying PCR, indicating their ability to produce AFs. Application of ELISA technique revealed AFs detection in 21(65.6%) samples of pistachios. The mean levels of AFs determined   were 6.06 and 12.08 μg/kg in fresh and salt roasted samples respectively. 19 (59.4%) of pistachio samples were exceed the maximum allowable limit set by the European union of total AFs concentration .Strong correlation obtained between AFs gene expression with AFs production. However, to avoid false negative and false positive results, applying more than one diagnostic molecular technique were suggested.